The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1542/peds.108.6.1287
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Factors Associated With Failure to Thrive in Children With Vertically Transmitted Human Immunodeficiency Virus-1 Infection: The Prospective, P2C2 Human Immunodeficiency Virus Multicenter Study

Abstract: Objective-Many children with human immunodeficiency virus-1 (HIV-1) have chronic problems with growth and nutrition, yet limited information is available to identify infected children at high risk for growth abnormalities. Using data from the prospective, multicenter P 2 C 2 HIV study, we evaluated the relationships between maternal and infant clinical and laboratory factors and impaired growth in this cohort.Methods-Children of HIV-1-infected women were enrolled prenatally or within the first 28 days of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
2
48
2
3
Order By: Relevance
“…3,4,9,[28][29][30] Factors that have been shown to influence growth during this period include viral burden, increased metabolic requirements during infection and neonatal nutrition. [31][32][33][34] Growth monitoring is routine and may provide a useful indicator for further diagnostic and treatment decisions. We found that breast-feeding was protective against mortality during the first 6 months of life in this cohort of HIV-1-infected children.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,9,[28][29][30] Factors that have been shown to influence growth during this period include viral burden, increased metabolic requirements during infection and neonatal nutrition. [31][32][33][34] Growth monitoring is routine and may provide a useful indicator for further diagnostic and treatment decisions. We found that breast-feeding was protective against mortality during the first 6 months of life in this cohort of HIV-1-infected children.…”
Section: Discussionmentioning
confidence: 99%
“…18 Initially, an American study evidenced decrease from 1 to 0.75 in the mean of weight-for-age z score during the whole follow-up period among HIV-infected children, but there was no significant statistical difference when compared to the HIV-exposed but uninfected children. 19 Nevertheless, an elegant American prospective study 20 demonstrated later that weight and height are significantly lower among HIV-infected children when compared to those values obtained from non-infected children belonging to the same socioeconomic status at 6 months of life. Such difference was correlated with the use of illicit drugs by the mother during pregnancy and other signs of AIDS-defining disease (pneumonia episodes, CD4 T-lymphocyte count and gression like other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Such difference was correlated with the use of illicit drugs by the mother during pregnancy and other signs of AIDS-defining disease (pneumonia episodes, CD4 T-lymphocyte count and gression like other studies. [20][21][22] Among the parameters derived from the CBC (total leukocyte count, TLC and hemoglobin level), only hemoglobin level at admission was useful to differentiate progressors from non-progressors in children older than 12 months. In the multivariate analysis, none of these parameters proved to be useful to predict risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies did not report differences between exposed and non-exposed infants. 7,8,11,15,17 However, one previous study reported a lower birth weight in exposed infants, 4 which was likely due to differences in the antiretroviral regimens. In the present study, the infants exposed to prophylactic treatment were heavier for their length than the children who were not exposed; this effect remained over time.…”
Section: Discussionmentioning
confidence: 99%